KAJIAN PERILAKU RUPTURE MELALUI SIMULASI NUMERIK - Indriyantho, Bobby Rio; Pamungkas, Aditya Sage; Lie, Han Ay; Sukamta, Sukamta (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
Concrete is very common material used in reinforced concrete structure. There are several behaviors that influence its performance to the structure since its nonlinear behavior (Nawy, 1998). Nonlinear concrete behavior, besides can be obtained by experimental test result in laboratory, also can be conducted with one of the numerical simulation approach, namely finite element method. Based on the case, it will be conducted numerical modeling of concrete material with input the nonlinearity and orthotropic of concrete. Load-displacement response of concrete without reinforcement at small loading tends to linear then will be nonlinear when enters the cracking zone. Möhr and Kupfer failure criteria are used to evaluate the failure in concrete beam. Validation is a step conducted to view the validity from numerical study result that will be used as tools. Data resulted from experimental and numerical study is validated with research of Purkiss-Blagojevic (1993). This FEM program can be used as tools to analyze load-displacement response of concrete beam test specimen without reinforcement and predict the initial crack pattern happened.